Constructing network enterprise structure to create innovative products - Yu. F. Telnov; V. M. Trembach; A. V. Danilov; E. V. Yaroshenko; V. A. Kazakov; O. A. Kozlova (Открытое образование (Москва), 2019)
The subject of the study  is the formation of the structure of a network enterprise, considered as a set of interacting enterprises in a networked Internet environment that implements a value chain. To build the structure of the network enterprise, it is proposed to use and support the ontology of the network enterprise, which conceptually reflects the models of products and related production and business processes throughout the life cycle. At the same time, the focus is on the implementation of flexible processes for creating innovative products using intelligent model-oriented technologies.The purpose of the study  is to build an algorithm for forming the structure of a network enterprise that would ensure the best implementation of the value chain with minimal risks of mismatch of designs and production processes with qualitative value characteristics and requirements for an innovative product. The construction of an algorithm for forming the structure of a network enterprise involves solving the problems of modeling the structure of an innovative product based on an analysis of qualitative value characteristics and requirements for product components, its creation processes, distribution of roles of enterprise participants and analysis of their capabilities.Methods. As the main research method is the method of constructing a model of “digital thread” of creating an innovative product. The most complete application of this method is carried out as part of the reference model of enterprise architecture for Industrie 4.0 (RAMI). The resulting conceptual model of an innovative product and related production and business processes is implemented using an ontological approach. It is proposed to use a combination of QFD (Quality Function Deployment) methods for deploying the structure of a network enterprise and analyzing the types and consequences of potential FMEA (Failure Mode and Effects Analysis) inconsistencies.The main results of the study are ontology and the algorithm for forming the structure of the network enterprise. A distinctive feature of the proposed ontology of the network enterprise is a clear separation of the valuable qualitative characteristics of the product and the requirements for its creation, as well as the allocation of the abilities of participants in enterprises to implement the necessary processes. The novelty of the presented algorithm for the formation of the structure of a network enterprise lies in the combined application of the QFD and FMEA methods, as well as in the iteration of modeling the structure of an innovative product from the position of the best implementation of quality value characteristics and functional requirements.Conclusions, prospects. The proposed algorithm for creating the structure of a network enterprise allows you to get the best decisions on the criterion for assessing the highest rating for the implementation of quality characteristics and requirements for the components of the value chain and its participants, provided that minimal risk assessments of the mismatch between the designs and processes of creating innovative products are obtained. The developed ontology and the algorithm for forming the structure of the network enterprise is of practical importance for creating an intelligent system for supporting the adoption of innovative decisions for the dynamic construction of network enterprises in the Internet environment.